A formação do fonoaudiólogo e suas práticas no atendimento a crianças surdas do sistema regular de ensino - Valente, Vivian Renate [UNIFESP] (2020)
Introduction: Based on the recontextualization of the human rights of people with disabilities and the Inclusive Education-based policymaking in Brazil, deaf children are enrolled in common classrooms in the regular education system. The inclusion of these children in regular schools demands a differentiated approach by the professionals involved so that these children are enabled to fully develop their potential. The speech therapist has a leading role in this context as a possible articulator of intersectoral actions between the child's school and health facilities. Objective: Understand how the students of the Speech Therapy course at UNIFESP perceive in their education the activities related to the care of deaf children inserted in the regular education system and attended at the Educational Audiology outpatient clinics and the Center for Interdisciplinary Care in Hearing, Language and Education. Methodology: Qualitative research, exploratory and descriptive, carried out with students of the Speech Therapy course working in the Educational Audiology outpatient clinics and in the Center for Interdisciplinary Care in Hearing, Language and Education of the Department of Speech Therapy at UNIFESP. For data collection, documental analysis of the Pedagogical Project and four focus groups with the students of the internship were carried out. Thematic content analysis was performed with the data obtained in the focus groups. Results: Through the analysis of the Pedagogical Project of the course, the subjects related to the theme Education were identified; the conceptual contents referring to the rights of people with disabilities; the actions taken by the students related to the schools of the children attended at the outpatient clinics. With the analysis of the focus groups, the students' perceptions emerged regarding the practices related to inclusive education carried out in the outpatient clinics, the perceptions regarding the role of speech therapy in the school inclusion process and about the concept of school inclusion. Conclusion: The educational process developed by the Speech Therapy students points to the need for curricular adjustments based on the assumptions of Special and Inclusive Education for deaf children, as well as on Interprofessional Education, which promote respect for difference, problematization and the development of collaborative practices and intersectoral.